Pengaruh Influencer Marketing dan Kepercayaan Konsumen terhadap Keputusan Pembelian Produk Fashion - Naufal, Dilif Faris; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Influencer Marketing and Consumer Trust on purchasing decisions for fashion products in e-commerce. The research method used is an associative quantitative approach. Data were collected through questionnaires distributed to 30 millennial respondents who actively use social media. Data analysis was conducted using Multiple Linear Regression with the help of EViews 12 software. The results showed that Influencer Marketing has a positive and significant effect on purchasing decisions. In addition, Consumer Trust was also proven to have a positive and significant effect on purchasing decisions. Simultaneously, the two independent variables contributed 94.94% of the influence on purchasing decisions. These findings indicate that the combination of authentic visual promotions from influencers and a strong foundation of trust is the main key to successful sales of fashion products in the digital era.